PKM Sosialisasi Intervensi Dini Anak Autis Melalui Penerapan Metode ABA kepada Guru-Guru SLB Jenne Tallasa Kabupaten Gowa - Usman Usman; Dwiyatmi Sulasminah; Purwaka Hadi (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
Abstract. Partners of the Community Partnership Program (PKM) are the Jene Tallasa Special School (SLB), Gowa Regency. The problems are: (1) Partners do not have good and correct insight and understanding about early intervention of students with Autism, (2) Partners have have a good and correct insight and understanding of the concepts and characteristics of children with autism, (3) Partners do not have the understanding and skills to apply the ABA method in early intervention in students with autism, while there are quite a lot of students with autism compared to children with special needs others at the school. The methods used are: lectures, discussions, brainstorming, question and answer and demonstrations. The results achieved are: (1) Partners have a fairly good insight and understanding of the nature and urgency of early intervention for students with Autism, (2) Partners already have good and correct insight and understanding of the concepts and characteristics of Autistic children, (3) Partners already have an understanding and are skilled enough to apply the ABA method in conducting early intervention on Autistic students.